Digital education for sustainable development in non-formal education in Germany and COVID-19-induced changes - Kohler, Florian; Kuthe, Alina; Rochholz, Fiona; Siegmund, Alexander (Sustainability, 2022)
Digital media increasingly transform daily routines as well as everyday actions and working environments, including education. Apps, games, computer programs, and social media, etc. can support and improve learning processes. The COVID-19 pandemic and the resulting restrictions of social life accelerated a shift towards the application of digital media in education as well as in distance learning. This paper answers questions about the current usage of digital media in non-formal education in Germany, especially in the context of Education for Sustainable Development (ESD). The results of a 2020 survey in Germany with 111 participants show that digital media are an integral part of non-formal education; in particular, audio and video recording and filesharing are used often. Notably, the usage of web calls and webinars has increased since the pandemic. Regarding the disadvantages of digitals formats, participants note the investment in time and effort as well as the expensive equipment needed for development. Despite being dissatisfied with existing offers, a lot of institutions have not developed their own digital education formats (yet). This indicates a possible need for further training and education of educators in non-formal ESD, enabling them to independently create digital formats. This would also contribute to the quality of digital formats, of which many were possibly developed without proper expertise.